EVALUASI USER INTERFACE WEBSITE E-COMMERCE DENGAN MENGGUNAKAN METODE HEURISTIC - Arif Aliyanto; Andri Wijaya; Alfonso Sitompul (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2022)
The development of e-commerce lately is very rampant, especially in Indonesia. With so many new business models emerging, making the business world full of variety and also inseparable from competition. A lot of e-commerce is based on a website that makes it easy for consumers and fulfills their needs. The e-commerce website that is the object of this research is shopee.com. The reason for choosing this website is because it is based on the ranking of the most frequently visited e-commerce websites on the iprice.co.id site. To find out the website is frequently visited, one of them is how attractive the interface of the website is to find out the truth, there are many methods used, one of which is the Heuristic Evaluation method. This method is used because this method has indicators that facilitate the analysis process. The results of this study can be seen that the criteria tested based on the Heuristic principle have all received a good response or agreed from the respondents and with these results for further research it can be increased to the maximum value.